Some Physical Development Indicators of Primary School-Aged Students in Rural Schools Conditions - Normurodovna Hazratova Нulkar (American Journal of Biodiversity, 2025)
In the article presents the results of a study of indicators of physical development of rural schoolchildren aged 7-10 years. According to the results obtained, the body weight, height and chest circumference of students increase depending on their age. In particular, in children 7-8 years old, the above indicators do not differ significantly from the norm. Boys and especially girls aged 9-10 years are distinguished by their height, chest circumference and Quetelet index, which are higher than normal. Studying the physical development of students is one of the important steps in further strengthening their health.